Impact of Pleurotus eryngii spent mushroom substrate on yield potentialand enzymatic activity in Pleurotus florida cultivation - Thakur, Preeti; Jandaik, Savita; Sharma, Annu (Mushroom Research, 2025)
This study investigated the effects of Pleurotus eryngii spent substrate (PESS) supplementation on the growth performance, yield, and enzymatic activity of Pleurotus florida. Wheat straw (WS) as a control (Control-2) demonstrated the fastest spawn run (18.25 days) and pinhead formation (22.38 days), while PESS alone (Control-1) showed the longest durations (28 days and 33.13 days, respectively). WS also produced the highest number of sporocarps (25.50) and achieved the highest yield (321.75 g/kg) and biological efficiency (107.25%). The combination of PESS, WS, wheat bran (WB), and calcium carbonate (CaCO3) (50:40:9.5:0.5) yielded 292 g/kg with 97.33% biological efficiency, while PESS alone resulted in the lowest yield (83.75 g/kg) and biological efficiency (27.91%). Enzymatic analysis revealed that laccase activity in WS was lowest during spawn run (0.09±0.03 and 0.35±0.00) but increased during pinhead initiation (0.83±0.00 and 1.16±0.00), peaking at fruit body maturation (2.05±0.00 and 3.47±0.00). A similar trend was observed in the PESS+WS+WB+CaCO3 combination. Xylanase activity followed a parallel pattern, with the lowest levels during the spawn run and the highest post-harvest. These findings emphasize the significant role of substrate composition and enzymatic activity in optimizing Pleurotus florida cultivation.